Removal of nutrients and pharmaceuticals and personal care products from wastewater using periphyton photobioreactors. (January 2018) - Kang, Du; Zhao, Qichao; Wu, Yonghong; Wu, Chenxi; Xiang, Wu
Highlights: Periphyton photobioreactors can simultaneously remove nutrients and PPCPs. Longer hydraulic retention time improve the performance of periphyton photobioreactors. Illumination showed different influences on nutrient and PPCP removal. Different operational conditions resulted in similar algal but contrasting bacterial community. Abstract: In this work, periphyton photobioreactors were built and were used for the treatment of synthetic wastewater spiked with PPCPs under different operational conditions. The removal rates of total nitrogen were relatively stable and varied from 39% to 77% overtime in different treatments. However, the removal rates of soluble reactive phosphorus decreased overtime from 42% to 68% on day 2 to 15.8% to 44% on day 22. For the selected PPCPs, only bisphenol A was effectively removed (72%–86.4%), hydrochlorothiazide and ibuprofen were moderately removed (26.2%–48.7%), and carbamazepine and gemfibrozil were poorly removed (6.45%–20.6%). Longer hydraulic retention time enhanced the treatment efficiency but illumination period showed contrasting effects on the removal of the nutrients and the PPCPs.